Kewenangan Diskresi Kepolisian Sebagai Sub-Unsur Struktur Sistem Peradilan Pidana di Indonesia - Yasa, Komang Danan Prayudhi Dharma; Sugama, I Dewa Gede Dana (Journal of Contemporary Law Studies, 2024)
The purpose of writing this scientific journal, among others, is to find out how the authority and discretionary weaknesses of the Police are as sub-elements of the structure of the criminal justice system in Indonesia, as well as the professionalism of the police in dealing with the weakness of discretionary authority based on the criminal justice system in Indonesia. A legal power known as discretion allows law enforcement officials, particularly police officers, to take action in unique circumstances in line with their own judgments and moral code. With an administrative and comparable approach, this paper employs an empirical legal research methodology. The results of the study show that the practice of applying discretion by the police is highly dependent on the subjectivity in question. Police professionalism is needed in order to carry out their duties properly as maintainers of security and order in society and as law enforcers.